Taj Mahal : an incredible love story : a graphic novel - Hoskin, Rik (Campfire graphic novels. History., 2019)
Presents the story of how and why the Taj Mahal was built--the Shah Jahan meets and falls in love with the beautiful Mumtaz Mahal, marrying her and making her the Mughal empress. Tragic circumstances cut their love short, and to honor her the Mughal emperor commissioned the building of the grand monument.